A single-blind study of podophyllotoxin cream 0.5% and podophyllotoxin solution 0.5% in male patients with genital warts. Issue 6 (December 1995) - Petersen, C S; Agner, T; Ottevanger, V; Larsen, J; Ravnborg, L
Abstract : OBJECTIVE--To evaluate the efficacy-safety ratio of a new topical podophyllotoxin cream 0.5% compared with podophyllotoxin solution 0.5% (Condyline) in male patients with genital warts. METHODS--In an observer-blinded controlled study a total of 136 and 133 wart lesions were treated with podophyllotoxin cream 0.5% and podophyllotoxin solution 0.5%, respectively. The preparations were applied twice daily for 3 days, repeated with 4 days intervals for a minimum of two and a maximum of four treatment cycles. RESULTS--At the conclusion of the study (8 weeks after completion of therapy) a significant reduction in mean wart area was observed in both the cream group (87.7, SD 8.4 to 20.6, SD 2.7) and in the solution group (92.3, SD 7.5 to 21.5, SD 2.8) (p < 0.01). At the same time all treated warts had completely cleared in 63% of patients in both study groups. Mild to moderate side effects occurred to the same extent in both podophyllotoxin cream and podophyllotoxin solution recipients. CONCLUSION--We conclude that podophyllotoxin 0.5% administered in a cream formulation does not give additional clinical benefits when compared with podophyllotoxin solution 0.5% in male patients with external genital warts.